Di Balik Gemerlap Pariwisata Upaya Komunitas Adat Bali Menjaga Eksistensi Subak sebagai Warisan Dunia - Deviana Rahayu; Sandi Kusuma (Journal of Community Development and Empowerment, 2026)
The Subak system in Bali, which has been recognized as a UNESCO World Heritage site, is currently facing serious threats due to massive land conversion and tourism commercialization. This community service activity aims to strengthen the existence of indigenous communities in maintaining the sustainability of Subak amidst the onslaught of modernization. The method used is Community-Based Development (CBD) through intensive mentoring, water management workshops, and the strengthening of awig-awig (customary regulations) related to agricultural land preservation. The results of the activity show that the active involvement of indigenous communities can increase collective awareness of the importance of maintaining the Tri Hita Karana philosophy as the foundation of Subak. Efforts to digitalize subak land mapping and develop community-based agritourism serve as strategic solutions to improve the economic well-being of farmers without damaging the local ecosystem. Furthermore, collaboration between krama subak (subak members) and policymakers successfully formulated a stricter draft for green zone protection. This community service concludes that empowering local communities is the primary key to maintaining Bali's cultural identity. Through the strengthening of customary institutions, Subak does not merely survive as a visual tourist attraction, but continues to function as a resilient religious-social irrigation system. The success of this program is expected to serve as a model for other regions in managing cultural heritage that intersects with the global tourism industry.